The Changing Dynamics of Family Structures - Sharma, Rashima (Trinity Law Review, 2026)
One of the most crucial sociodemographic variables for comprehending individual health disparities is family. The impact of family as a social determinant of health-on health outcomes is still substantial and constant, even in the face of major changes in family structure in recent decades. The influence of family ties on an individual’s health and vice versa emphasizes how multifaceted health is, involving both objective and subjective factors. Every stage of life, from early childhood to old age, the family’s dynamics and structure have a big impact on a person’s social, mental, and physical health. Therefore, by visualizing a conceptual model of an individual’s health within the family, this paper aims to investigate how the family, with its structure and dynamics, reflects on people’s health and health behaviour from early childhood through adulthood and into old age in the context of significant life events or transitions like marriage, divorce, widowhood, and parenthood.